1999
DOI: 10.1161/01.cir.100.suppl_2.ii-275
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Best Treatment for Uncomplicated Patients With Type B Acute Aortic Dissection : A Consideration for Sound Surgical Indication

Abstract: Background-In the treatment of type B acute aortic dissection without complications, better results are obtained if surgery is performed before enlargement of the aorta in patients who are predicted to show aortic enlargement and if drug-based treatment is continued for patients who are predicted to show no enlargement. The purpose of this study was to predict the acute-phase factors that may affect chronic-phase aortic enlargement by studying chronic-phase enlargement of dissections in patients without compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
123
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 11 publications
(11 reference statements)
7
123
1
1
Order By: Relevance
“…COPD indicates chronic obstructive pulmonary disease; BP, blood pressure. 12 Although the results in these 2 articles were different, our results support the latter. In this study, the presence of COPD was not a significant risk factor for increase in the diameter in the univariate or multivariate analysis (Table 2).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…COPD indicates chronic obstructive pulmonary disease; BP, blood pressure. 12 Although the results in these 2 articles were different, our results support the latter. In this study, the presence of COPD was not a significant risk factor for increase in the diameter in the univariate or multivariate analysis (Table 2).…”
Section: Discussionsupporting
confidence: 55%
“…6,7,12,14,15 These results can be explained by the La Place Law. 4,6 It states that the perpendicular stress on a cylinder is directly proportional to the pressure exerted by the fluid contents and its radius and is inversely proportional to wall thickness.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Several studies have reported that patent false lumen is an important prognostic factor in patients with aortic dissection. [10][11][12] Early death occurred in 5 patients (3.9%) in the thrombosed group and 6 (5.9%) in the patent group. This difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Several studies have reported that early or late complications such as aortic rupture and organ ischemia are related to whether the false lumen has been thrombosed or remains patent. 10,11) Akutsu, et al reported that a patent false lumen is strongly associated with late aortic events and mortality. 12) However there are few reports focusing on the false lumen of acute type B dissection in relation to early and late outcomes.…”
Section: Introductionmentioning
confidence: 99%